Tuning Crystal Ordering, Electronic Structure, and Morphology in Organic Semiconductors: Tetrathiafulvalenes as a Model Case - Pfattner, Raphael; Bromley, Stefan T.; Rovira, Concepció; Mas-Torrent, Marta (Advanced functional materials, 2016)
Tetrathiafulvalenes (TTFs) are an appealing class of organic small molecules giving rise to some of the highest performing active materials reported for organic field effect transistors (OFETs). Because they can be easily chemically modified, TTF‐derivatives are ideal candidates to perform molecule–property correlation studies and, especially, to elucidate the impact of molecular and crystal engineering on device performance. A brief introduction into the state‐of‐the‐art of the field‐effect mobility values achieved with TTF derivatives employing different fabrication techniques is provided. Following, structure–performance relationships are discussed, including polymorphism, a phenomenon which is crucial to control for ensuring device reproducibility. It is also shown that chemical modification of TTFs has a strong influence on the electronic structure of these materials, affecting their stability as well as the nature of the generated charge carriers, leading to devices with p‐channel, n‐channel, or even ambipolar behaviour. TTFs have also shown promise in other applications, such as phototransistors, sensors, or as dopants or components of organic metal charge transfer salts used as source–drain contacts. Overall, TTFs are appealing building blocks in organic electronics, not only because they can be tailored to perform fundamental studies, but also because they offer a wide spectrum of potential applications. Tetrathiafulvalenes are promising active materials in organic field‐effect transistors (OFETs), in which they exhibit high performances. An overview is provided of the use of this family of materials as a model building block for OFETs to highlight general concepts of organic semiconductors and their use in devices.